Gastroparesis in Non-Diabetics: Associated Conditions and Possible Risk Factors - Nassar, Yousef (Gastroenterology Res, 2018)
BACKGROUND: Gastroparesis is a syndrome characterized by delayed gastric emptying in the absence of any mechanical cause. While often associated with diabetes mellitus, most cases of gastroparesis are idiopathic. The purpose of the present paper is to review the co-morbid conditions that most likely associate with non-diabetic gastroparesis. METHODS: The Healthcare Cost and Utilization Project: Nationwide Inpatient Sample (HCUP-NIS) data were used from the year 2013 - 2014 and the Apriori algorithm was run on this subset of patients to identify what co-morbid conditions are most likely associated with gastroparesis. RESULTS: Notable conditions that were found to be most closely linked with gastroparesis were: chronic pancreatitis, end stage renal disease, irritable bowel syndrome, systemic lupus erythematosus, fibromyalgia, and venous thromboembolism. Some of the implications of these findings are briefly discussed. CONCLUSIONS: Gastroparesis is strongly associated with multiple medical conditions which may be potential targets for treatment.